Identification of a Promiscuous Epitope Peptide Derived From HSP70. Issue 7 (September 2019) - Matsui, Hiroto; Hazama, Shoichi; Tamada, Koji; Udaka, Keiko; Irie, Atsushi; Nishimura, Yasuharu; Miyakawa, Tomoya; Doi, Shun; Nakajima, Masao; Kanekiyo, Shinsuke; Tokumitsu, Yukio; Shindo, Yoshitaro; et al.
Abstract : We previously found that heat-shock protein 70 (HSP70) is expressed on hepatocellular carcinoma cells and developed an HSP70 mRNA-transfected dendritic cell therapy for treating unresectable or recurrent hepatocellular carcinoma. The phase I trial was completed successfully. The purpose of this study is to identify a promiscuous epitope peptide derived from HSP70 for the purpose of developing a novel cancer peptide vaccine. Using a computational algorithm to analyze the specificity of previously reported major histocompatibility complex class I–binding peptides, we selected candidates that bound to >2 of the 3 HLA types. Twenty-nine HSP70-derived peptides (9-mers) that bound to HLA-class I was selected. The peptides were prioritized based on the results of peptide binding experiments. Using dendritic cells stimulated with the candidate peptide described previously as stimulators and CD8 + T cells as effectors, an ELISPOT assay was performed. Cytotoxicity of CD8 lymphocytes stimulated with the candidate peptides toward HSP70-expressing cancer cells was analyzed using an xCELLigence System. Peptides were administered to HLA-A 24 transgenic mice as vaccines, and peptide-specific T-cell induction was measured in vivo. We identified a multi-HLA-class I–binding epitope peptide that bound to HLA-A*02:01, *02:06, and *24:02 in vitro using an interferon-γ ELISPOT immune response induction assay. Cytotoxicity was confirmed in vitro, and safety and immune response induction were confirmed in vivo using HLA-A 24 transgenic mice. Our study demonstrated that the promiscuous HSP70-derived peptide is applicable to cancer immunotherapy in patients with HLA-A*24:02-positive, *02:01-positive, and *02:06-positive HSP70-expressing cancers. Abstract : Supplemental Digital Content is available in the text.